(untitled) (Medico Legal Update, 2021)
Forensic experts are often in confrontation with the challenging task of determination of stature along with race, age etc. for the purpose of establishing the identity of the deceased individual in those circumstances where only skeletal remains, mutilated or dismembered body parts, extremely decomposed body parts etc. are provided by investigating authorities. In the current study, a genuine attempt has been made to arrive at the population specific regression equation for stature prediction from the percutaneous length of Tibia. The subjects chosen for this study include 120 adult males belonging to Tamil population falling within the age range of 21 to 30 years. Stature and percutaneous lengths of right and left Tibia from each subject were precisely recorded following standard protocols using appropriate instruments and analysis of the data collected was done applying Pearson correlation through SPSS software version 26 to arrive at the regression equations for stature assessment based on percutaneous right and left Tibial lengths respectively. By comparing the regression formulae obtained from the present study with those derived from various population specific studies done on Indian population, our regression equations found to be distinctive to Tamil population and therefore can be authentically applied for calculation of stature of deceased from percutaneous Tibial length in males of Tamil population whenever skeletal remains are available.